2008
DOI: 10.1016/j.brainres.2007.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes changes ionotropic glutamate receptor subunit expression level in the human retina

Abstract: Early diabetic retinopathy is characterized by changes in subtle visual functions such as contrast sensitivity and dark adaptation. The outcome of several studies suggests that glutamate is involved in retinal neurodegeneration during diabetes. We hypothesized that the protein levels of ionotropic glutamate receptor subunits are altered in the retina during diabetes. Therefore, we investigated whether human diabetic patients have altered immunoreactivity of ionotropic glutamate receptor subunits in the retina.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…From a molecular biology standpoint, diabetes has been shown to alter the levels and receptors of several inner retinal neurotransmitters (most notably dopamine and gamma-aminobutyric acid [GABA]), as early as 4 weeks post-STZ. 30,51,52 Cellularly, increased cell death of amacrine and ganglion cells has been observed within weeks of STZ injection. 28,33 Functionally, other ERG studies have reported dysfunction in amacrine-and ganglion cell-dominated OPs and scotopic threshold response (STR) at 4 weeks post-STZ.…”
Section: Retinal Origins Of Visual Defects In Diabetesmentioning
confidence: 98%
“…From a molecular biology standpoint, diabetes has been shown to alter the levels and receptors of several inner retinal neurotransmitters (most notably dopamine and gamma-aminobutyric acid [GABA]), as early as 4 weeks post-STZ. 30,51,52 Cellularly, increased cell death of amacrine and ganglion cells has been observed within weeks of STZ injection. 28,33 Functionally, other ERG studies have reported dysfunction in amacrine-and ganglion cell-dominated OPs and scotopic threshold response (STR) at 4 weeks post-STZ.…”
Section: Retinal Origins Of Visual Defects In Diabetesmentioning
confidence: 98%
“…These elevated concentrations of extracellular and synaptic glutamate in the retina lead to the so-called ‘excitotoxicity’ in which the excess of glutamate stimulation causes an uncontrolled intracellular calcium response in postsynaptic neurons that results in cell death 50. The excitoxicity of glutamate is the result of overactivation of ionotropic glutamate receptors, mainly α-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate (AMPA) and N-methyl- d -aspartame (NMDA), which have been found to be overexpressed in streptozotocin-induced diabetic rats 52 53. There are at least two mechanisms involved in glutamate-induced apoptosis: a caspase-3-dependent pathway and a caspase-independent pathway involving calpain and mitochondrial apoptosis-inducing factor 54…”
Section: Pathogenic Mechanisms Involved In Retinal Neurodegenerationmentioning
confidence: 99%
“…The results showed that the immunoreactivity of GluR2 and NR1 subunits was significantly increased by diabetes. 61 Studies in diabetic rats also indicated that immunoreactivity of AMPA and NMDA receptor subunits Glu2/3 and NMDA1 were increased. 62 In addition, one of these studies indicated that AMPA receptor subunit GluR2 phosphorylation and cellular distribution were altered during the early stages of diabetes, perhaps reflecting a shift in receptor recycling.…”
Section: Glutamate Excitotoxicitymentioning
confidence: 99%